Integrated Serosurveillance of Infectious Diseases Using Multiplex Bead Assays: A Systematic Review - Selina Ward; Harriet L. S. Lawford; Benn Sartorius; Colleen L. Lau (Tropical Medicine and Infectious Disease)
Integrated serological surveillance (serosurveillance) involves testing for antibodies to multiple pathogens (or species) simultaneously and can be achieved using multiplex bead assays (MBAs). This systematic review aims to describe pathogens studied using MBAs, the operational implementation of MBAs, and how the data generated were synthesised. In November and December 2023, four databases were searched for studies utilising MBAs for the integrated serosurveillance of infectious diseases. Two reviewers independently screened and extracted data regarding the study settings and population, methodology, seroprevalence results, and operational implementation elements. Overall, 4765 studies were identified; 47 were eligible for inclusion, of which 41% (n = 19) investigated multiple malaria species, and 14% performed concurrent surveillance of malaria in combination with other infectious diseases (n = 14). Additionally, 14 studies (29%) investigated a combination of multiple infectious diseases (other than malaria), and seven studies examined a combination of vaccine-preventable diseases. Haiti (n = 8) was the most studied country, followed by Ethiopia (n = 6), Bangladesh (n = 3), Kenya (n = 3), and Tanzania (n = 3). Only seven studies were found where integrated serosurveillance was the primary objective. The synthesis of data varied and included the investigation of age-specific seroprevalence (n = 25), risk factor analysis (n = 15), and spatial analysis of disease prevalence (n = 8). This review demonstrated that the use of MBAs for integrated surveillance of multiple pathogens is gaining traction; however, more research and capabilities in lower- and middle-income countries are needed to optimise and standardise sample collection, survey implementation, and the analysis and interpretation of results. Geographical and population seroprevalence data can enable targeted public health interventions, highlighting the potential and importance of integrated serological surveillance as a public health tool.